Ascorbic acid retention of calamansi (Citrus microcarpa Bunge) nectar - Malabanan, Maria Merced U. (2002)
ABSTRACT The retention of ascorbic acid in the processing of calamansi nectar in relation to pH and titratable acidity was studied. The determination of three parameters, namely, pH, titratable acidity and ascorbic acid content was made at four different stages in the processing - fresh juice extract, before pasteurization, after pasteurization, and after 24 hours of storage. The analyses were also done on the juice prepared from the nectar. Ascorbic acid content was determined using the 2,6-dichlorophenolindophenol (DPIP) visual titration method. Results showed that the amount of ascorbic acid declined with processing and storage. The retention of ascorbic acid in the finished product, from its initial value of 40.51 mg/100 g (pure calamansi extract) to final values of 14.64 mg/100g - 16.67 mg/100g (processed calamansi nectar) ranged from 32.53% - 37.04%.